Estudo do procedimento de recuperação por soldagem de ferramentas de estampagem do aço VF800AT - Pellin, Adonis (2018)
In this work a procedure was developed to recover components of welding stamping tools with the GMAW - MAG process made of VF800AT steel and evaluated the performance in the industry, compared between new punches and recovered by welding. In welding of specimens and punches, the wire used for the deposition of the martensitic alloy is classified by DIN 8555 as MF6-GF-60-GP, with a nominal diameter of 1.2 mm. The specimens were processed under the following conditions: condition 1 (preheating temperature 450 °C), condition 2 (preheating temperature 500 °C) and condition 3 (preheating temperature 550 °C), all with a tempering and condition 4 (preheat temperature 450 °C) with two tempering. The quality of the welds was determined by non-destructive tests, macrography, micrography and microhardness Vickers HV 0.1 kgf. The results of non-destructive tests were approved for all conditions. The micrographs show the microstructures formed in the regions of the weld and the microhardness profiles show that the solder metal of conditions 1, 2 and 3 the values specified by the consumable supplier. For ZAC, conditions 1 and 2 meet the values specified for tempered and tempered base material, and for condition 3 the result is above the specified value and for the base material the values do not meet those specified. The values for condition 4, the solder metal ZAC and base material do not meet the specifications, but the hardness of the base material is equal to conditions 1, 2 and 3. The performance test in the industry with weld repaired punches was satisfactory, with the cutting edge radius Δr 4.8% and the maximum deviation Rz 5.5% higher than the values found for the new punches, proving that the punches repaired by welding have the same performance as new punches. It was verified that the main conclusion of this research is that condition 1 presented the best results, being the most suitable to recover components of stamping tools made of VF800AT steel by welding, followed by conditions 2 and 3.